2022
DOI: 10.1128/spectrum.01185-22
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Genomic Insights of the Unexplored Porcine Pathogen Actinobacillus pleuropneumoniae Using Whole Genome Sequencing

Abstract: Pleuropneumonia is one of the most relevant respiratory infections in the swine industry. Despite Actinobacillus pleuropneumoniae (APP) being one of the most important pathogens in the pig production, this is the first comparative study including all available whole genome sequencing data from NCBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…In the latter study, isolate origins included Australia, Asia, Europe, and North and South America, and comprised a range of serovars, i.e., 1-2, 4-8, and 10-11. All the serovar 11 (like 3457) isolates predicted to have active phage were from Europe, although the serovar 1 (like 3459) isolate was from China [9]. Whilst neither of these studies has shown active phage, our results suggest that the presence of Mu-like phage, especially ones related to Mannheimi a Vb, is comparatively common in A. pleuropneumoniae genomes.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In the latter study, isolate origins included Australia, Asia, Europe, and North and South America, and comprised a range of serovars, i.e., 1-2, 4-8, and 10-11. All the serovar 11 (like 3457) isolates predicted to have active phage were from Europe, although the serovar 1 (like 3459) isolate was from China [9]. Whilst neither of these studies has shown active phage, our results suggest that the presence of Mu-like phage, especially ones related to Mannheimi a Vb, is comparatively common in A. pleuropneumoniae genomes.…”
Section: Discussionmentioning
confidence: 71%
“…Phastest did not predict an attachment site for PluMu 3457 or PluMu 3459, unsurprising given the lack of knowledge of A. pleuropneumoniae phage biology. Others have used Phaster [10], or another phage identification program Prophage Hunter [9] to search A. pleuropneumoniae genomes for complete and/or active phage. Whole genome analysis identified 13 “complete” [10], and 21 “active” phages with 18 being most closely related to Mannheimia Vb [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actinobacillus pleuropneumoniae is an important swine pathogen responsible for respiratory infectious disease, porcine contagious pleuropneumonia (PCP). PCP is characterized by fibrinous, hemorrhagic, and necrotic lung lesions, and causes substantial losses in the swine industry worldwide (Guitart-Matas et al, 2022;Zhang et al, 2022). To date, 19 reference serovars have been identified based on the composition of the capsular polysaccharide (CPS; Stringer et al, 2021;Scherrer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%